Strategi Pengembangan Bisnis Agroteknologi Agri Edu Pariwisata Pertanian Kabupaten Sumedang - Dicky Kurniawan; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Agus Mulyana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Indonesia, as an agricultural country ranked 51st out of 78 countries in the 2021 Food Sustainability Index (FSI) and with a low performance in the Sustainable Agriculture category (ranked 71st), faces serious challenges in global food security due to the lack of accurate agricultural land data. This problem hinders efforts to achieve the Sustainable Development Goals (SDGs), particularly SDG 2 on zero hunger for food security and nutrition, and SDG 12 on sustainable consumption and production in the efficient use of resources. To overcome this, the Precision Agriculture Ecosystem Map has emerged as an innovative solution, integrating IoT devices, Edge Computing, and Artificial Intelligence (AI) for GIS-based plantation mapping. This system provides farmers with accurate information on land characteristics, crop requirements, planting season determination, and recommendations for fertilization and irrigation, and even predicts the risk of crop failure. This innovation is expected to increase agricultural productivity in a sustainable manner, optimize resource use, reduce waste, and significantly contribute to national food security and farmer welfare.